e-technologies and networks for development first international conference, ICeND 2011, Dar-es-Salaam, Tanzania, August 3-5, 2011. proceedings - Yonazi, Jim James; Sedoyeka, Eliamani; Ariwa, Ezendu; El-Qawasmeh, Eyas (Communications in computer and information science, 2011)
This book constitutes the proceedings of the First International Conferences on e-Technologies and Networks for Development, ICeND 2011, held in Dar-es-Salaam, Tanzania, in August 2011. The 29 revised full papers presented were carefully reviewed and selected from 90 initial submissions. The papers address new advances in the internet technologies, networking, e-learning, software applications, Computer Systems, and digital information and data communications technologies - as well technical as practical aspects.